High efficient dual band stacked antennas integrated into rescue helmets for indoor communication. Issue 10 (15th December 2021) - Islam, Hashinur; Das, Saumya; Bose, Tanushree; Dhar, Sourav
Abstract: A dual-band stacked antenna integrated with a rescue helmet is proposed for WLAN applications. The cross slot aperture feeding technique enables the antenna to support dual-band operation at 2.4 and 5 GHz. On the ground plane, two slots are formed, perpendicular to each other and of different lengths. Four dielectric layers of different permittivity are stacked over this cross slot to attain the desired frequency bands. Under free space condition, the radiator yields 7% (2.31–2.48 GHz), 15.87% (5.12–6 GHz) 10 dB return loss bandwidth (BW). The use of low loss dielectric layers on the slots also provides a high antenna efficiency and moderate gain at both frequency bands. The small dimension of antenna encourages its use as a wearable helmet antenna. Antenna performances are observed under wearable condition. For assessing human exposure to RF electromagnetic fields, SAR evaluations are conducted at both 2.4 and 5 GHz WLAN bands.